Prospective analysis of 30-day postoperative adverse events in skull base surgery: insights into risk factors and mitigation strategies from a neurosurgical tertiary care center - Grutza, Martin; Bächler, Hendrik; Haux-Nettesheim, Daniel; Lenga, Pavlina; Suchorska, Bogdana; Scherer, Moritz; Krieg, Sandro; Walter, Johannes; Dao Trong, Huy Philip (Neurosurgical review, 2025)
Introduction Skull base surgery presents significant challenges due to the complex anatomy and proximity of tumors to critical neurovascular structures. While advancements in surgical techniques have improved outcomes, the risk of postoperative adverse events (AEs) remains substantial. This study provides a prospective analysis of AEs and associated risk factors in skull base surgery, leveraging data from a high-volume tertiary neurosurgical center. The analysis focuses on tumor location, surgical craniotomies, and patient-specific factors to identify predictors of complications and guide risk mitigation strategies. Methods Between January 2022 and December 2023, 236 adult patients undergoing skull base surgery were prospectively enrolled. AEs—defined as any complication occurring within 30 days postoperatively—were systematically documented. Data collection included patient demographics, tumor characteristics, surgical craniotomies, intraoperative findings, and postoperative outcomes to identify risk factors for AEs. Statistical analyses were performed to assess associations between these variables and postoperative complications. Results The study cohort had a mean age of 56.8 ± 12.7 years, with tumor distribution supratentorial (55.1%) and infratentorial (44.9%). The most frequently utilized surgical craniotomies were retrosigmoid (40.3%), pterional (39.4%), and later lateral supraorbital (6.4%). Overall, 28.8% of patients experienced AEs, with 22.5% neurosurgical (e.g., new-onset cranial nerve deficits) and 8.5% non-neurosurgical (e.g., thromboembolic events, infections). Older age and higher ASA scores (p = 0.01) were significant predictors of non-neurosurgical AEs. Revision surgery was required in 6.8% of cases. Infratentorial tumor location and prolonged operative times were strongly associated with an increased risk of surgical complications (p = 0.001), while the retrosigmoid craniotomy was a key risk factor for both neurosurgical AEs and revision surgeries (p = 0.001). ROC analysis showed that combining age and ASA score improved prediction of non-neurosurgical AEs (combined AUC = 0.78 vs. age AUC = 0.70; ASA AUC = 0.72). Conclusion Our findings highlight critical and actionable risk factors influencing neurosurgical outcomes. We demonstrate that infratentorial tumor location and prolonged surgical duration significantly increase the likelihood of surgery-related adverse events, with the retrosigmoid craniotomy particularly elevating these risks. Notably, advanced age and higher ASA scores robustly predict non-surgery-related complications, with a combined predictive accuracy superior to each factor individually. These insights underscore the importance of meticulous preoperative risk assessment and tailored surgical strategies, enabling clinicians to proactively manage high-risk patients and improve postoperative outcomes.